New tools, technology and techniques applied to geological sciences: current situation and future perspectives - Ulloa, Andrés (2014)
Nowadays the technological advances are revolutionizing the way and efficiency of work and its impact is being reflected in the geological sciences. The new microelectromechanical systems allow the incorporation of a wide variety of sensors in devices such as smartphones and tablets. These instruments are multifunctional and highly portable for data collection in field geology and replace others devices in the field as personal computers and PDA. Nowadays, high precision GPS in conjunction with LIDAR technology and sonar technology are more accessible for geological research. With this technology is possible to generate high-resolution three-dimensional models to complement geological studies. A remote sensing technique like high penetration radar is used for modeling ice thickness and bedrock topography in Antarctic. Modern tridimensional scanning and printing techniques are used in geological research and teaching. Also the advance in computer technology allows handling three-dimensional models on personal computers very efficiently and with different display options